Being Prepared During the Evolving COVID-19 Pandemic: A Neonatal Experience in Training and Simulation - Juin Yee Kong; Juin Yee Kong; Juin Yee Kong; Juin Yee Kong; Srabani Samanta Bharadwaj; Srabani Samanta Bharadwaj; Srabani Samanta Bharadwaj; Srabani Samanta Bharadwaj; Amutha Chinnadurai; Amutha Chinnadurai; Selina Kah Ying Ho; Selina Kah Ying Ho; et al. (Frontiers in Pediatrics, 2021)
Background: Rapid spread of the COVID-19 pandemic raised an urgent need for preparedness in the healthcare sector, including training of healthcare workers to cope with the burden of infected cases while ensuring proper protection of themselves. Improper infection prevention and control measures were key reasons for infection in healthcare workers during the early phase of the outbreak.Objectives/Methods: This paper describes the combined approach of 3 restructured hospitals in Singapore in preparing and training neonatal healthcare workers' during the COVID-19 pandemic crisis, as well as lessons learnt during this process.Results: Information sharing was conducted in the form of e-learning, emphasizing on topics like disease knowledge and infection prevention and control procedures. Skills and competency training were carried out in the form of simulation, with sessions scaled into 4 levels progressing from individual task training to larger group simulations involving multiple disciplines and departments. Challenges encountered included information fatigue by large amount of constantly changing information and multiple amendments to workflows as more information arose. Difficulties conducting training and simulation sessions included restriction of group size to mitigate infection risk amongst participants and the limited supply of personal protective equipment prioritized for direct patient care.Conclusion: Healthcare institutions should ensure adequate dissemination of conceptual knowledge as well as skills competency training of staff in infection control measures for the protection of healthcare workers and patient safety. Ongoing training for sustainability of knowledge and skills, while adapting to the rapidly evolving situation is important in the preparation for future outbreaks.